1987
DOI: 10.1073/pnas.84.7.1992
|View full text |Cite
|
Sign up to set email alerts
|

Tandem linkage and unusual RNA splicing of the T-cell receptor beta-chain variable-region genes.

Abstract: The variable-region (V) genes of the murine MATERIALS AND METHODS Construction and Screening of Genomic and cDNA Libraries. Construction and screening of C57BL/6 and SJL genomic libraries and of a C57BL/6 spleen cDNA library were performed as described (13). The nucleotide sequence of relevant portions of cloned DNA was determined by either the method of Maxam and Gilbert (14) or the chain-termination method of Sanger et al. (15).Hybridization of Genomic DNA Fragments. High molecular weight DNA from C57BL/6 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 31 publications
3
38
1
Order By: Relevance
“…V05.1 and V05.2 are considered together together since these genes are homologous and the hybridization conditions used in these experiments do not distinguish them. V1,5.3, a related pseudogene (38), is not detected under these conditions (data not shown). Considering the total number of singly expressed V3 genes in the three hybridoma panels, V,5.1 and V15.2 comprise 12%, 9.1%, and 0.6% of the expressed Vp genes in B10 (H-2b), B10.Q (H-2q), and B10.BR (H-2k) mice, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…V05.1 and V05.2 are considered together together since these genes are homologous and the hybridization conditions used in these experiments do not distinguish them. V1,5.3, a related pseudogene (38), is not detected under these conditions (data not shown). Considering the total number of singly expressed V3 genes in the three hybridoma panels, V,5.1 and V15.2 comprise 12%, 9.1%, and 0.6% of the expressed Vp genes in B10 (H-2b), B10.Q (H-2q), and B10.BR (H-2k) mice, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Among 1900 hybrids we have examined (Table 2; unpublished observations), only 6 (0.3%) were found that express Va7 genes. (23,38). The data in Table 3 These differences are statistically significant [B1O.Q vs. B1O.BR (P < 0.0004) and B10 vs. B1O.BR (P < 0.05)].…”
mentioning
confidence: 80%
“…BC, BV, and BJ primer sequences were as described earlier (18), except BV8.3 (TGCTGGCAACCTTCAAAT AGGA) and BV13 (AGGCCTAAAGGAACTAACTCCAC). As BV5.3 (22), BV17 (23), and BV19 (24) are not functional in B10.D2 mice, they were not amplified. BV-BJ repertoires were analyzed for BV2, BV3, BV4, BV5.1, BV6, BV7, BV8.1-3, BV9, BV14, and BV16 genes.…”
Section: Tcrb Repertoirementioning
confidence: 99%
“…Northern blots containing SL12.4 poly(A)+ RNA were hybridized with a C,31-specific probe. Figure 1B shows that there was no evidence for mature 1.3- were derived either from published work (1,8,14) or from our sequence analysis of the expressed V35.1 element in SL12.4 cells.…”
mentioning
confidence: 96%